Peningkatan Sistem Manajemen Peserta Didik dalam Instansi Pendidikan (SD, TK TPQ) Di Nagari Riak Danau Tapan - Salsabilah, Sholyha; Wisda, Rini Syevyelni; Anwar, Khairul (Institut Agama Islam Negeri Kerinci, 2021)
This research aims to identify and analyze the challenges faced in the student management system in educational institutions in Nagari Riak Dananu Tapan as well as to design and implement improvement strategies to increase the effectiveness of the system. The research method used is a qualitative approach through special studies. Data was collected through observations, interviews and document analysis. The results of the research show that schools in Nagari Riak Danau Tapan experience several obstacles including a lack of integrity between various system modules, a lack of integration between various system modules, a lack of active involvement from stakeholders and the need for increased training for staff.